Investigation of the antioxidant capacity of the components of Astragalus after membrane separation - Wang Yandong; Guo Yafei; Wang Yingli; Zhang Zemin (E3S Web of Conferences, 2020)
Astragalus is commonly used in health supplements, and its flavonoids and saponins are the important material basis for immune system enhancement. The study on the effective component contents and antioxidant capacities of astragalus extract after membrane separation lays the foundation of the application of membrane separation technology in health supplement development. The astragalus extract was filtered by suction and passed through membranes of 10000 Da, 2500 Da, and 600 Da to obtain retentate 1 (M1), retentate 2 (M2), retentate 3 (M3) and permeate MT. UV/vis spectrophotometer was used to compare the contents of total flavonoids and total saponins before and after each step of membrane separation. High performance liquid chromatography (HPLC) was used to analyze the contents of Verbasil Glucoside and Astragaloside IV of all membrane separation samples, and the antioxidant activities were determined. The contents of flavonoids in membrane separation samples were significantly different. In the freeze-dried powders obtained from the membrane separation, the contents of total flavonoids and Verbasil Glucoside were the lowest in MT, M1 was the highest, and M3 was the second highest. The order of contents of total saponins and Astragaloside IV of the freeze-dried powders from membrane separation was as follows: M3 > M1 > M2 > MT. Among them, the content of total saponins in the freeze-dried powder of M3 was the highest, which reached 2.67 times of that of the astragalus extract. The order of the scavenging activities of membrane separation samples for DPPH free radical was: MT > M3 > M2 > M1 > astragalus extract. The strongest scavenging activity of hydroxyl free radicals was found in M3, and the scavenging rates of hydroxyl free radicals in all samples were higher than those of VC. The total antioxidant capacity of FRAP showed a certain dose-effect relationship. At the same concentration, the FRAP values of M1 and MT were higher than other samples. Membrane separation technology can be used to separate and purify the effective components from astragalus extract. M3 has the highest contents of the total flavonoids and total saponins, and its antioxidant capacity is better than that of astragalus extract and other samples obtained by membrane separation.